Efficacy of combining aspirin with hydroxychloroquine in pregnancies at high risk for pre-eclampsia: a prospective, multicentre, open-label, single-arm clinical trial, investigator-initiated study (HUGS study) - Hyun-Hwa Cha; Suk-Joo Choi; Soo-young Oh; Cheong-Rae Roh; Ji-Hee Sung; Won Joon Seong; Yoo-Min Kim; Jisu Seong; Ji Hoi Kim; Gina Nam; Gwang jun Kim (BMJ Open)
Introduction The use of hydroxychloroquine (HCQ) during pregnancies complicated by systemic lupus erythematosus or refractory antiphospholipid antibody syndrome has demonstrated a significant ability to prevent pre-eclampsia (PE). As such, the potential for the administration of HCQ to prevent PE in other high-risk pregnancies is an important clinical research agenda among maternal and fetal medicine specialists. Mechanistically, the anti-inflammatory and immunomodulatory effects of HCQ can offer vascular protection and inhibit the placental dysfunction-associated thrombotic changes underlying the pathophysiology of PE, fetal growth restriction (FGR) and fetal death in utero (FDIU). Placenta-mediated complications exhibit a distinctive overlapping syndrome between pregnancies, and low-dose aspirin is the only prevention method currently in use. This study investigated the effects of improvements in outcomes with HCQ administration in high-risk pregnancies complicated by a previous experience of PE, FGR or FDIU.Methods and analysis This multicentre, open-label, single-arm trial commenced on 31 May 2022, in three tertiary hospitals in Korea. Pregnant women with a prior history of PE, FGR or FDIU are eligible to participate. This single-arm study set the previous study with the most similar inclusion criteria, aspirin dose and drug administration period as the comparison group. The required sample size was determined to be 58, with an expected dropout rate of 10%.Ethics and dissemination This study protocol was approved by the following institutions and committees: Institutional Review Boards of Chung-Ang University Gwangmyeong Hospital (2304-082-056), Samsung Medical Center (2021-11-087-003) and Kyungpook National University Chilgok Hospital (2021-06-005-006) and the Ministry of Food and Drug Safety. The results will be disseminated to the general public, grant funder, maternal–fetal medicine specialists and other researchers.Trial registration number NCT05287321.